Perancangan Film Dokumenter Motif Tenun Khas Jepara sebagai Media Edukasi - Saifur Rauf; Handry Rochmad Dwi Happy (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2020)
The purpose of this study was to design a documentary video of Jepara's weaving motif as an educational media, while reminding the government would be important to maintain local cultural heritage. Methodology in this study was observations carried out at Kartini and Omah Petrok homes in Jepara with a length of observation 2 semesters, interviews made to get data directly from sources, and literature studies obtained from the results of reading books and journal articles that have relationships with theory and the object of basic studies in the study. The results of this study documentaries that have been made and in screening have been going well. From the delivery of the audience understood the contents of the documentary and so tofu Kalua Jepara weaving still had no own typical motives. Based on the overall questionnaire showed very good results. Therefore the manufacture of documentaries in Jepara weaving motifs can be accepted among teenagers and adults aged 15-45 years.